Penerapan Arsitektur High Tech pada Sirkuit Motocross di Kabupaten Jeneponto - Munandar, Moch.Aris; Tauhid, Fahmyddin A'raaf; Nursyam, Nursyam (The Department of Architecture, Faculty of Science and Technology, Universitas Islam negeri Alauddin Makassar, 2026)
Motocross circuits are essential sports facilities that foster the skills and creativity of young automotive enthusiasts; however, designs that neglect functionality, safety, and aesthetics often reduce user comfort and experience. This study aims to design a Motocross Circuit in Jeneponto Regency using a high-tech architecture approach to enhance functionality, aesthetics, and technological innovation in the building. The method includes a literature review to gather theories on motocross circuits and high-tech principles, previous studies to evaluate forms, structures, and facilities of similar projects, and field observation to analyze site conditions and accessibility. The design results feature an integrated site plan, Pit Building, and spectator stands utilizing Space Frame structures, metal and glass materials, and an efficient, safe circulation system. The design emphasizes transparency, exposed structural elements, and interactivity, supporting both racing activities and automotive education while creating a futuristic visual experience and strong site identity. This approach enables the circuit to function as a safe, comfortable, and innovative educational and recreational facility for both visitors and participants.